2017
DOI: 10.1111/ina.12438
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of weatherization on indoor air quality: A field study of 514 homes

Abstract: Residential energy efficiency retrofits continue to be common in the United States, especially through governmental and utility programs. Because of the potential for reduced air exchange, there have been concerns raised regarding the potential for negative impacts on health and safety of residents when air sealing occurs. To address this concern, a study was undertaken in 2009-2010 to evaluate the indoor air quality impacts of weatherization performed through the U.S. Department of Energy's Weatherization Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…These were described in 44 papers plus two reports treated as equivalent to supplemental information, with up to five papers providing results of a study. The extracted and included data represented 15 studies of basic retrofits [4,8,10,19,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], four studies of ventilation-added retrofits [19,[37][38][39][40], four studies of green retrofits [41][42][43][44][45], and 13 studies of warmth retrofits [7,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Most of the studies were conducted in the United States or Europe, with two studies in New Zealand [7,50].…”
Section: Resultsmentioning
confidence: 99%
“…These were described in 44 papers plus two reports treated as equivalent to supplemental information, with up to five papers providing results of a study. The extracted and included data represented 15 studies of basic retrofits [4,8,10,19,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], four studies of ventilation-added retrofits [19,[37][38][39][40], four studies of green retrofits [41][42][43][44][45], and 13 studies of warmth retrofits [7,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Most of the studies were conducted in the United States or Europe, with two studies in New Zealand [7,50].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 650 radon-tested energy-efficient dwellings, Minergie labelled buildings (M) accounted for 37% (217), and the remaining 433 homes were part of the national energy renovation program (Programme Bâtiment) for buildings (R). It is noteworthy that out of the 217 M buildings, most were newly built (NM, 182) and only 35 were renovated (RM), illustrated in Figure 1.…”
Section: Characteristics Of Selected Dwellingsmentioning
confidence: 99%
“…A recent study by Meyer [34] reported two times higher radon concentrations in retrofitted houses than in passive homes in Germany. A significant increase in indoor radon concentrations owing to energy retrofits was also observed in dwellings in the USA [35] and Lithuania [36]. In the case study by Jiránek and Kačmaříková [37], addition of an exterior thermal insulation in homes and retrofitting windows led to 3.4 times higher radon concentration.…”
mentioning
confidence: 93%
“…An indoor air quality (IAQ) assessment conducted as part of a national WAP evaluation found that over 300 homes weatherized in 2010 and 2011 saw a statistically significant increase of 0.44 picocuries per liter (pCi/L) [16.2 Becquerels/cubic meter (Bq/m 3 )] (26%) in control‐adjusted indoor radon concentration at the lowest occupied/occupiable level of the home, with a 90 percent confidence interval of ±0.22 pCi/L (±8.1 Bq/m 3 ) . One‐third of these homes had a basement as the lowest living level and the other two‐thirds had the first floor (defined as the first floor above the foundation space, which is either a crawl space or basement) as the lowest living level.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored changes in radon and moisture levels in homes undergoing energy retrofits using current energy upgrade strategies and evaluated the impacts on radon levels from targeted radon migration prevention measures. The WAP IAQ Study evaluated impacts from energy retrofits that did not include required ventilation, well‐installed ground covers, or other targeted radon measures. This study employed a controlled pre/post‐intervention design to determine whether simple, inexpensive measures implemented in the context of energy retrofits help limit radon exposures and excessive moisture.…”
Section: Introductionmentioning
confidence: 99%